Oncologic Trends, Outcomes, and Risk Factors for Locoregional Recurrence: An Analysis of Tumor-to-Nipple Distance and Critical Factors in Therapeutic Nipple-Sparing Mastectomy. Issue 6 (June 2019) - Frey, Jordan D.; Salibian, Ara A.; Lee, Jiyon; Harris, Kristin; Axelrod, Deborah M.; Guth, Amber A.; Shapiro, Richard L.; Schnabel, Freya R.; Karp, Nolan S.; Choi, Mihye
Abstract : Background: Oncologic outcomes with nipple-sparing mastectomy continue to be established. The authors examine oncologic trends, outcomes, and risk factors, including tumor-to-nipple distance, in therapeutic nipple-sparing mastectomies. Methods: Demographics, outcomes, and overall trends for all nipple-sparing mastectomies performed for a therapeutic indication from 2006 to 2017 were analyzed. Oncologic outcomes were investigated with specific focus on recurrence and associated factors, including tumor-to-nipple distance. Results: A total of 496 therapeutic nipple-sparing mastectomies were performed, with an average follow-up time of 48.25 months. The most common tumor types were invasive carcinoma (52.4 percent) and ductal carcinoma in situ (50.4 percent). Sentinel lymph node sampling was performed in 79.8 percent of nipple-sparing mastectomies; 4.1 percent had positive frozen sentinel lymph node biopsy results, whereas 15.7 percent had positive nodal status on permanent pathologic examination. The most common pathologic cancer stage was stage IA (42.5 percent) followed by stage 0 (31.3 percent). The rate of local recurrence was 1.6 percent ( n = 8), and the rate of regional recurrence was 0.6 percent ( n = 3). In all, 171 nipple-sparing mastectomies had magnetic resonance imaging available with which to assess tumor-to-nipple distance. Tumor-to-nipple distance of 1 cm or less (25.0 percent versus 2.4 percent; p = 0.0031/ p = 0.1129) and of 2 cm or less (8.7 percent versus 2.0 percent; p = 0.0218/ p = 0.1345) trended to higher rates of locoregional recurrence. In univariate analysis, tumor-to-nipple distance of 1 cm or less was the only significant risk factor for recurrence (OR, 13.5833; p = 0.0385). No factors were significant in regression analysis. Conclusions: In early stage and in situ breast carcinoma, therapeutic nipple-sparing mastectomy appears oncologically safe, with a locoregional recurrence rate of 2.0 percent. Tumor-to-nipple distances of 1 cm or less and 2 cm or less trended to higher recurrence rates. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III. Abstract : Patient Safety CME.